Nascent RNA sequencing identifies a widespread sigma70-dependent pausing regulated by Gre factors in bacteria - Zhe Sun (Nature Portfolio, 2021)
Transcription by bacterial RNA polymerase is interrupted by pausing events that play diverse regulatory roles. Here, the authors find that a large number of E. coli sigma70-dependent pauses, clustered at a 10−20-bp distance from promoters, are regulated by Gre cleavage factors constituting a mechanism for rapid response to changing environmental cues.